2020
DOI: 10.3390/diagnostics10060371
|View full text |Cite
|
Sign up to set email alerts
|

KCTD15 Protein Expression in Peripheral Blood and Acute Myeloid Leukemia

Abstract: Leukocytes are major cellular components of the inflammatory and immune response systems. After their generation in the bone marrow from hematopoietic stem cells, they maturate as granulocytes (neutrophils, eosinophils, and basophils), monocytes, and lymphocytes. The abnormal accumulation and proliferation of immature blood cells (blasts) lead to severe and widespread diseases such as leukemia. We have recently shown that KCTD15, a member of the potassium channel tetramerization domain containing protein famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Starting from our recent observation that KCTD15 is upregulated in both B-ALL 9 and AML cell lines 10 and patient-derived samples, we here found an intriguing link between the upregulation of the protein and the activation of the NF-κB pathway that was observed in different contexts and conditions. In a first instance, the transient silencing of KCTD15 in MLL-rearranged leukemia model systems (RS4;11 and SEM) induced cell death and apoptosis with a significant downregulation of pIKK-β, the kinase deputed to the activation of the NF-κB pathway 9 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Starting from our recent observation that KCTD15 is upregulated in both B-ALL 9 and AML cell lines 10 and patient-derived samples, we here found an intriguing link between the upregulation of the protein and the activation of the NF-κB pathway that was observed in different contexts and conditions. In a first instance, the transient silencing of KCTD15 in MLL-rearranged leukemia model systems (RS4;11 and SEM) induced cell death and apoptosis with a significant downregulation of pIKK-β, the kinase deputed to the activation of the NF-κB pathway 9 .…”
Section: Discussionmentioning
confidence: 76%
“…Very recently, we have found that KCTD15, a member of the emerging family of the KCTD (potassium channel tetramerization domain) proteins 8 , is upregulated in patients and cell lines of both childhoods B-cell ALL 9 and AML 10 . Moreover, this protein also displays a characteristic and well-defined profile of expression in peripheral blood cells (granulocytes, monocytes, and lymphocytes), thus suggesting that it plays an active role in both physiological and pathological processes, although the mechanism underlying this activity is yet to be uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…The KCTD family of proteins have been reported to be involved in a variety of regulatory processes, including γ-aminobutyric acid type B signaling, proteasome processes, potassium transport and regulation of transcription response (57). Previous studies have demonstrated that these proteins are closely associated with the progression of cancer, including acute myeloid leukemia (58), breast cancer (59) and medulloblastoma (60). KCTD20, encoded on chromosome 6, is an isoform of BTBD10 and harbors a C-terminal amino acid sequence similar to that of BTBD10 (61).…”
Section: Discussionmentioning
confidence: 99%
“…Natural mutants of KCTD1 have been demonstrated to be the causative agents of the scalp-ear-nipple syndrome [7,16] whereas KCTD15 inhibits the Hedgehog pathway in medulloblastoma cells [8]. We have recently shown that KCTD15 is overexpressed in patients and cell lines of both childhood B-cell acute lymphoid leukemia and acute myeloid leukemia [17,18]. We have also shown that KCTD15 also displays a characteristic and well-defined profile of expression in peripheral blood cells (granulocytes, monocytes, and lymphocytes) [17].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that KCTD15 is overexpressed in patients and cell lines of both childhood B-cell acute lymphoid leukemia and acute myeloid leukemia [17,18]. We have also shown that KCTD15 also displays a characteristic and well-defined profile of expression in peripheral blood cells (granulocytes, monocytes, and lymphocytes) [17]. Although the biochemical role(s) underlying this assortment of biological functions are yet to be uncovered, the observation that KCTD15 silencing-induced apoptosis and cell death in leukemia cell suggesting that it has a role in cellular homeostasis and proliferation prompted us an analysis of the KCTD15 expression levels in other oncological conditions.…”
Section: Introductionmentioning
confidence: 99%